Nikephoros Bryennios the Younger – the First One Not to Become a Blind Man? Political and Military History of the Bryennios Family in the 11th and Early 12th Century - Böhm, Marcin (Studia Ceranea, 2020)
Nikephoros Bryennios the Younger has a place in the history of Byzantium as the author of one of the works devoted to the Komnenos family coming to power. This outstanding observer and talented leader, who was fascinated by the person of his father-in-law Alexius I Komnenos, came from a family whose ambitions were no less than the those in the one into which Nikephoros himself married. His father and grandfather, also his namesake, were those who dreamed of an imperial crown for themselves and tried to reach for it armed. Apart from defeat, they both faced punishment which was blinding. One of those who captured and ordered the father of Nikephoros the Younger to be blinded was his future father-in-law. Like the later marriage with Anna Komnene, this had an impact on the respect he had for the new dynasty. However, the question is whether this respect should be explained by the man’s reluctance to participate in a plot against his brother-in-law that his ambitious wife and her mother planned.